The number of years lost in 30-year work life spans of people with type 1 and type 2 diabetes. (30th September 2020) - Nexø, M A; Pedersen, J; Andersen, I; Cleal, B; Bjørner, J B
Abstract: Background: Although diabetes is among the most common causes of lifelong disability, no studies have yet outlined work disability from a life course perspective. This study estimated the number of years people with type 1 and type 2 diabetes lost in a work life span compared to people without diabetes Methods: Individuals aged 18-65 years, diagnosed with type 1 (n = 33, 188) or type 2 diabetes (n = 81, 930) were identified from national registers from the entire Danish population and age and gender matched with controls without diabetes (n = 663, 656), for period 2000-2017. WLE in years were estimated as time in employment from age 35 to 65. We used a life table approach with multi-state Cox proportional hazard modelling (95% Confidence Intervals: CI). Age was the underlying time-axis. Inverse probability weights accounted for differences between populations. Analyses were performed separately for sex, educational status, and types of diabetes in 5-year age intervals. Results: Individuals with type 1 diabetes and type 2 diabetes had significantly shorter WLE compared to people without diabetes in the 30-year span. Type 1 diabetes: WLE ranged from 8 years shorter among women with short education [-8.0; CI:-11/-5.0] to 4 years shorter [-4.4; CI:-6.6/-2.3] with high education; WLE in men ranged from -6.4 [CI:-8.7/-4.0] with short education to -3.0 [CI:-4.5/-1.5] with high education. Type 2 diabetes: WLE ranged from -6.5 [CI: -8.9/-4.0] in women with short education to -2.9 [CI: -4.5/-1.3] with high education. WLE in men ranged from -7.0 [CI: -9.4/-4.5] with short education to -3.7 [CI: -5.4/-2.0] with high education. Conclusions: The substantial number of years lost in a work life span for individuals with type 1 or type 2 diabetes, highlight need for new strategies that prevent work disability, particularly for individuals with short education. Key messages: Individuals with type 1 diabetes and type 2 diabetes had between 9 and 3 years shorter work life expectancies compared to people without diabetes in a 30-year span. The work life spans are substantial shorter for individuals with type 1 or type 2 diabetes with short educations.